Kerangka Pemberantasan Korupsi Di Usa Dan Dampaknya - Ang Prisila Kartin (JEMAP, 2018)
United States is well-known as a superpower country. Among all the countries in the world United States has the best economic strength, military power, and political power. But it is not in line with the Corruption Perceptions Index which indicates how corrupt their public sectors are seen to be. The rampant corruption in United States happened in both of government sector and the private sector. Some cases that have occurred are the Watergate Scandal, Lockheed Scandal, Enron, WorldCom, and Xerox. Various cases of corruption in the United States indicate that superpower country supported by strong economic, military and political conditions does not necessarily make the cases of corruption / frauds in the country to be disappear. United States needs to make efforts to eradicate corruption in the country to suppress possible corruption cases.Various efforts made by the United States in the form of law issuance and the establishment of corruption eradication agencies are expected to help overcome the problem of corruption in the world. The United States, as the axis of the world's economy and politics, has caused many countries to be affected by the enactment of anti-corruption laws. The global awareness in eradicating corruption is expected to bring a positive climate for the global economy to realize a prosperous world community